Preparation method of super-strong and super-tough conductive hydrogel for retarding crack growth by submicron carbon clusters

By using submicron carbon clusters in the hydrogel, the problem of insufficient mechanical properties and toughness of traditional hydrogels is solved by pinning cracks and entangling polymer chains, and the preparation of high-performance ultra-strength super-tough conductive hydrogels is achieved.

CN119842015AActive Publication Date: 2025-04-18SOUTHWEST FORESTRY UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510078704.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

Traditional hydrogels have shortcomings in mechanical properties and toughness, which limits their application in load-bearing materials. The nanoparticles are incompatible with the hydrogel precursor solution, resulting in uneven distribution and unable to effectively enhance the performance of the hydrogel.

Method used

By mixing sodium carboxymethylcellulose, dopamine and solvent, a submicron carbon cluster solution was prepared and polymerized with acrylamide monomer and initiator to prepare a super-strong super-tough conductive hydrogel with submicron carbon clusters to slow crack propagation.

Benefits of technology

The submicron carbon clusters effectively slow down crack propagation by pinning cracks and entangling polymer chains, significantly improving the mechanical strength and toughness of the hydrogel. Through excellent interfacial interaction and electrical conductivity, they promote the uniform distribution of nanoparticles and enhance the performance of the hydrogel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842015A_ABST
    Figure CN119842015A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of super-strong and super-tough conductive hydrogel for retarding crack growth through submicron carbon clusters, and belongs to the technical field of hydrogel materials. The preparation method of the super-strong and super-tough conductive hydrogel comprises the following steps: mixing sodium carboxymethyl cellulose, dopamine and a solvent, and carrying out heat treatment to obtain a submicron carbon cluster solution; and mixing the submicron carbon cluster solution, an acrylamide monomer and an initiator, and carrying out polymerization reaction to obtain the super-strong and super-tough conductive hydrogel. In order to improve the mechanical property of the hydrogel, a novel nano-cluster is designed to serve as a nano-filler, the high-performance crystal hydrogel is prepared by utilizing the pinning effect of the submicron carbon cluster on cracks, and the submicron carbon cluster can effectively slow down crack propagation by pinning the cracks and entangling polymer chains in the stretching process, so that the mechanical property of the hydrogel is improved. The stress concentration of the crack tip is relieved, and the notch sensitivity is eliminated, so that the mechanical strength of the hydrogel is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogel materials, and more specifically relates to a method for preparing a super-strong and super-tough conductive hydrogel with submicron carbon clusters for slowing down crack extension. Background Art

[0002] Due to its excellent flexibility and biocompatibility, hydrogels have shown great potential in the fields of human-machine interface, flexible electronics and soft robots, which require materials to have excellent mechanical properties and toughness. However, traditional hydrogels usually show brittle or soft characteristics and lack effective energy dissipation mechanisms, resulting in low mechanical properties and toughness, which limits their application in load-bearing materials. In order to improve the toughness of hydrogels, researchers design specific mechanisms at the microscopic or macroscopic level. A common method is to construct special structures, such as oriented nanofiber structures and nanocrystalline domains. These structures make the energy required for destruction much higher than that of conventional hydrogels. Crystallized hydrogels, as modified hydrogels, significantly enhance their mechanical properties and toughness by introducing crystals. Crystals act as highly cross-linked agents, strengthen the structure of hydrogels, and provide them with additional support. During the stretching process, crystals strengthen the polymer chains and slow down the propagation of cracks through the pinning effect, thereby achieving a toughening effect. In addition, the introduction of crystalline domains can also adjust the network structure of hydrogels and affect their hydration. In some cases, crystallization controls the expansion rate and degree of the hydrogel by restricting the entry of water molecules into the crystalline region, giving it morphological stability and avoiding excessive expansion or water loss during long-term use. Researchers have prepared high-strength crystalline hydrogels through methods such as directional freezing, salting out, and solvent exchange. However, these methods increase crystallinity through polymer chain aggregation and rapid network shrinkage, resulting in a decrease in the water content of the hydrogel, and most of them use complex production processes, and many processes are only applicable to specific hydrogel systems. How to design a single-network hydrogel with both mechanical properties and toughness remains a huge challenge.

[0003] Introducing the interfacial effect between nanoparticles and polymers can effectively improve the mechanical properties and toughness of hydrogels. The rich functional groups on the surface of nanoparticles interact with polymer chains, and non-covalent crosslinking enhances the mechanical strength of hydrogels. However, most nanoparticles are incompatible with hydrogel precursor solutions, resulting in uneven distribution and inability to effectively enhance the performance of hydrogels. In addition, the high cost of nanoparticles and the complex synthesis process limit the development of nanocomposite hydrogels. Therefore, it is of great significance to develop a super-strong and super-tough conductive hydrogel. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a super-strong and super-tough conductive hydrogel with submicron carbon clusters to slow down crack propagation, so as to solve the problems existing in the above-mentioned prior art and realize the preparation of super-strong and super-tough conductive hydrogel.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is to provide a method for preparing a super-strong and super-tough conductive hydrogel with submicron carbon clusters to slow down crack propagation, comprising the following steps:

[0007] Sodium carboxymethyl cellulose, dopamine and a solvent are mixed and then heat-treated to obtain a submicron carbon cluster solution;

[0008] The submicron carbon cluster solution, acrylamide monomer and initiator are mixed and then subjected to polymerization reaction to obtain the super-strong and super-tough conductive hydrogel.

[0009] In order to improve the mechanical properties of hydrogel, the present invention designs a new type of nanocluster to act as a nanofiller, and prepares high-performance crystalline hydrogel by utilizing the pinning effect of submicron carbon clusters on cracks. The submicron carbon clusters can effectively slow down crack propagation, relieve stress concentration at the crack tip, and eliminate notch sensitivity by pinning cracks and entangled polymer chains during the stretching process, thereby significantly improving the mechanical strength of the hydrogel.

[0010] As a new type of carbon nanomaterial, submicron carbon clusters have excellent optical properties, non-toxicity, biocompatibility and solubility. In addition, submicron carbon clusters have a spatial structure different from carbon dots and can produce similar effects to crystals. More importantly, submicron carbon clusters are easy to prepare and have SP 2 The crystal nuclei endow the material with excellent conductivity and interfacial interactions (such as π-π stacking, CH-π, etc.), thereby improving the compatibility of nanoparticles (submicron carbon clusters) with the hydrogel precursor solution, promoting the uniform distribution of nanoparticles, and effectively enhancing the performance of the hydrogel.

[0011] In addition, the heat-treated carbonized sodium carboxymethyl cellulose and dopamine can well retain the active functional groups of the carbonized precursors, ensuring that the prepared submicron carbon clusters have good dispersibility. The use of them to prepare hydrogels introduces a large number of physical cross-linking reaction sites into the hydrogels, giving the hydrogels ultra-high tensile strength and toughness.

[0012] Preferably, the solvent comprises water.

[0013] Preferably, the dosage ratio of the sodium carboxymethyl cellulose, dopamine and solvent is 0.5 g:0.5 g:100 mL.

[0014] Preferably, the heat treatment temperature is 160° C. and the heat treatment time is 1 hour.

[0015] The present invention can achieve the effect of slowing down crack propagation by controlling the dosage ratio of raw materials and the parameters of heat treatment during the preparation of submicron carbon clusters; wherein, when the dosage of sodium carboxymethyl cellulose is high, it will lead to too many backbones of carbon clusters, thereby reducing the fracture energy, and a low dosage will lead to dopamine as the main body, which also fails to achieve the purpose of slowing down crack propagation.

[0016] Preferably, the acrylamide monomers include acrylamide and N,N-methylenebisacrylamide, and the mass ratio of acrylamide to N,N-methylenebisacrylamide is 2.5:0.004.

[0017] Preferably, the initiator comprises 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.

[0018] Preferably, the mass ratio of the submicron carbon cluster solution, acrylamide monomer and initiator is 5.625-9.375:2.5:0.05.

[0019] Preferably, the polymerization reaction conditions are: UV light conditions, the light intensity is 70mw / m 3 , temperature is 25±5℃, time is 2min.

[0020] The present invention can adjust the mechanical properties of the hydrogel by controlling the dosage ratio of the raw materials in the hydrogel preparation process; wherein, when the dosage of the submicron carbon clusters is high, the fracture stress and elongation of the hydrogel will be greatly reduced, and when the dosage is low, the submicron carbon clusters will only play the role of nanofillers, making the hydrogel brittle.

[0021] The second technical solution of the present invention is to provide a super strong and super tough conductive hydrogel prepared by the above preparation method.

[0022] The third technical solution of the present invention is to provide the application of the above-mentioned super-strong and super-tough conductive hydrogel in the fields of human-computer interaction interface, flexible electronics and soft robots.

[0023] The present invention discloses the following technical effects:

[0024] 1. The submicron carbon clusters that can slow down crack propagation and prepare super-strong and super-tough conductive hydrogels according to the present invention are made of sodium carboxymethyl cellulose and dopamine. The submicron carbon clusters can effectively slow down crack propagation by pinning cracks and entangled polymer chains during the stretching process, thereby constructing a hydrogel with super-strong mechanical properties;

[0025] 2. The submicron carbon clusters prepared by the present invention not only have sp 2The crystal nuclei can give the material good interface interactions (such as π-π stacking, CH-π, etc.), and the heat-treated carbonized sodium carboxymethyl cellulose and dopamine can well retain the functional groups of the carbonized precursors, ensuring that the prepared submicron carbon clusters have good dispersibility. The use of them to prepare hydrogels introduces a large number of physical cross-linking reaction sites into the hydrogels, giving the hydrogels ultra-high tensile strength and toughness;

[0026] 3. The submicron carbon clusters obtained by the present invention are flower-like cluster structures, which can have entanglement with the long polymer chains and slow down crack propagation (e.g. Figure 6 and Figure 7 shown). BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The stress-strain curves and partial magnified diagrams of the hydrogels prepared in Example 1 and Comparative Examples 1 to 6;

[0028] Figure 2 The stress-strain curves of the hydrogels prepared in Example 1 and Comparative Examples 9-10;

[0029] Figure 3 The stress-strain curves of the hydrogels prepared in Examples 1 to 3, wherein 1% is Example 1, 0.75% is Example 2, and 1.25% is Example 3;

[0030] Figure 4 The stress-strain curves of the hydrogels with gaps prepared in Examples 1 to 3 and Comparative Examples 1, 4, 5, and 6;

[0031] Figure 5 is the fracture energy of the hydrogels prepared in Examples 1 to 3 and Comparative Examples 1, 4, 5, and 6;

[0032] Figure 6 TEM image of the submicron carbon cluster solution obtained in Example 1;

[0033] Figure 7 Schematic diagram of the preparation process of the ultra-strong and ultra-tough conductive hydrogel that uses submicron carbon clusters to slow down crack propagation. DETAILED DESCRIPTION

[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0035] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0039] Unless otherwise specified, the room temperature involved in the present invention is 25±5°C.

[0040] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present invention are all commercially available products.

[0041] Example 1

[0042] Preparation of super strong and super tough conductive hydrogel with submicron carbon clusters to slow down crack propagation, the specific steps are as follows:

[0043] S1. Add 0.5 g sodium carboxymethyl cellulose and 0.5 g dopamine into 100 mL deionized water, place in a pressure-resistant reaction bottle, heat to 160 ° C for 1 h, and cool the reaction container naturally to room temperature to obtain a submicron carbon cluster solution (CCs);

[0044] S2, CCs (7.5 g), acrylamide (2.5 g), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (0.05 g) and N,N-methylenebisacrylamide (4 mg) were mixed evenly, and then irradiated with ultraviolet light at 25 ° C for 2 min to obtain the ultra-strong and ultra-tough conductive hydrogel PAM-CCs (CCs-1%, m CMC :m DA =1:1).

[0045] Example 2

[0046] The preparation of polyacrylamide-0.75% carbon nanocluster hydrogel, the specific steps are:

[0047] S1. Add 0.375 g sodium carboxymethyl cellulose and 0.375 g dopamine into 100 mL deionized water, place in a pressure-resistant reaction bottle, heat to 160 ° C for 1 h, and cool the reaction container naturally to room temperature to obtain a carbon nanocluster solution (CCs);

[0048] S2. CCs (7.5 g), acrylamide (2.5 g), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (0.05 g) and N,N-methylenebisacrylamide (4 mg) were mixed evenly, and then irradiated with ultraviolet light for 2 min at 25°C to obtain an ultra-strong and ultra-tough conductive hydrogel (CCs-0.75%) with carbon nanoclusters that slow down crack propagation.

[0049] Example 3

[0050] Preparation of polyacrylamide-1.25% carbon nanocluster hydrogel, the specific steps are:

[0051] S1. Add 0.625 g sodium carboxymethyl cellulose and 0.625 g dopamine into 100 mL deionized water, place in a pressure-resistant reaction bottle, heat to 160 ° C for 1 h, and cool the reaction container naturally to room temperature to obtain a carbon nanocluster solution (CCs);

[0052] S2. CCs (7.5 g), acrylamide (2.5 g), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (0.05 g) and N,N-methylenebisacrylamide (4 mg) were mixed evenly, and then irradiated with ultraviolet light for 2 min at 25°C to obtain an ultra-strong and ultra-tough conductive hydrogel (CCs-1.25%) with carbon nanoclusters that slow down crack propagation.

[0053] Comparative Example 1

[0054] The preparation of polyacrylamide hydrogel, the specific steps are:

[0055] Deionized water (7.5 g), acrylamide (2.5 g), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (0.05 g) and N,N-methylenebisacrylamide (4 mg) were mixed evenly and irradiated with ultraviolet light for 2 min at 25°C to obtain polyacrylamide hydrogel (PAM).

[0056] Comparative Example 2

[0057] The preparation of polyacrylamide-dopamine hydrogel includes the following specific steps:

[0058] Deionized water (7.5 g), acrylamide (2.5 g), dopamine (0.075 g), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (0.05 g) and N,N-methylenebisacrylamide (4 mg) were mixed evenly and irradiated with ultraviolet light for 2 min at 25°C to obtain polyacrylamide-dopamine (PAM-DA).

[0059] Comparative Example 3

[0060] The preparation of polyacrylamide-sodium carboxymethyl cellulose hydrogel includes the following specific steps:

[0061] Deionized water (7.5 g), acrylamide (2.5 g), sodium carboxymethyl cellulose (0.075 g), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (0.05 g) and N,N-methylenebisacrylamide (4 mg) were mixed evenly and irradiated with ultraviolet light for 2 min at 25°C to obtain polyacrylamide-sodium carboxymethyl cellulose (PAM-CMC).

[0062] Comparative Example 4

[0063] The preparation of polyacrylamide-sodium carboxymethyl cellulose-dopamine hydrogel comprises the following specific steps:

[0064] Deionized water (7.5 g), acrylamide (2.5 g), sodium carboxymethyl cellulose (0.0375 g), dopamine (0.0375 g), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (0.05 g) and N,N-methylenebisacrylamide (4 mg) were mixed evenly, and then irradiated with ultraviolet light for 2 min at 25°C to obtain polyacrylamide-sodium carboxymethyl cellulose (PAM-CMC-DA).

[0065] Comparative Example 5

[0066] The preparation of polyacrylamide-dopamine carbon dot hydrogel, the specific steps are:

[0067] S1. Add 1 g of dopamine into 100 mL of deionized water, place the mixture in a pressure-resistant reaction bottle, heat it to 160° C. and react for 1 h. The reaction vessel is naturally cooled to room temperature to obtain a dopamine carbon dot solution.

[0068] S2. After dopamine carbon dot solution (7.5 g), acrylamide (2.5 g), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (0.05 g) and N,N-methylenebisacrylamide (4 mg) were mixed evenly, polyacrylamide-dopamine carbon dot hydrogel (PAM-CDA) was prepared after irradiation with ultraviolet light for 2 min at 25°C.

[0069] Comparative Example 6

[0070] The preparation of polyacrylamide-sodium carboxymethyl cellulose carbon dot hydrogel, the specific steps are:

[0071] S1. Add 1 g of sodium carboxymethyl cellulose to 100 mL of deionized water, place the mixture in a pressure-resistant reaction bottle, heat it to 160° C. and react for 1 h. The reaction vessel is naturally cooled to room temperature to obtain a sodium carboxymethyl cellulose carbon dot solution.

[0072] S2. Mix the sodium carboxymethyl cellulose carbon dot solution (7.5 g), acrylamide (2.5 g), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (0.05 g) and N,N-methylenebisacrylamide (4 mg) evenly, and irradiate with ultraviolet light for 2 min at 25°C to obtain polyacrylamide-sodium carboxymethyl cellulose carbon dot hydrogel (PAM-CCMC).

[0073] Comparative Example 7

[0074] The preparation of polyacrylamide-carbon nanocluster (the mass ratio of sodium carboxymethyl cellulose to dopamine is 2:1) hydrogel, the specific steps are as follows:

[0075] S1. Add 0.67 g sodium carboxymethyl cellulose and 0.33 g dopamine into 100 mL deionized water, place in a pressure-resistant reaction bottle, heat to 160° C. and react for 1 h. The reaction container is naturally cooled to room temperature to obtain a carbon nanocluster solution.

[0076] S2, CCs (7.5 g), acrylamide (2.5 g), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (0.05 g) and N,N-methylenebisacrylamide (4 mg) were mixed evenly, and then irradiated with ultraviolet light at 25 ° C for 2 min to obtain an ultra-strong and ultra-tough conductive hydrogel (m CMC :m DA =2:1).

[0077] Comparative Example 8

[0078] The preparation of polyacrylamide-carbon nanocluster (the mass ratio of sodium carboxymethyl cellulose to dopamine is 1:2) hydrogel, the specific steps are as follows:

[0079] S1. Add 0.33 g of sodium carboxymethyl cellulose and 0.67 g of dopamine into 100 mL of deionized water, place in a pressure-resistant reaction bottle, heat to 160° C. and react for 1 h. The reaction container is naturally cooled to room temperature to obtain a carbon nanocluster solution.

[0080] S2, CCs (7.5 g), acrylamide (2.5 g), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (0.05 g) and N,N-methylenebisacrylamide (4 mg) were mixed evenly, and then irradiated with ultraviolet light at 25 ° C for 2 min to obtain an ultra-strong and ultra-tough conductive hydrogel (m CMC :m DA =1:2).

[0081] Effect verification:

[0082] The hydrogels prepared in Examples 1 to 3 and Comparative Examples 1 to 8 were subjected to mechanical property testing, toughness calculation and fracture energy calculation as follows:

[0083] 1. The hydrogels prepared in Examples 1 to 3 and Comparative Examples 1 to 8 were cut into rectangular specimens (4 cm×2 mm×1 mm) and subjected to tensile property tests at room temperature.

[0084] The uniaxial tensile measurements were performed using an electronic universal testing machine (Suntech Technology Co., Ltd., Shenzhen, China) with an extension speed of 80 mm / min.

[0085] Toughness is the area under the stress-strain curve and is calculated as follows:

[0086] ΔU = ∫σdε;

[0087] Where σ and ε are the stress and strain of the hydrogel, respectively.

[0088] The results are shown in Table 1 and Figures 1 to 3 shown.

[0089] 2. The hydrogels prepared in Examples 1, 2, 3 and Comparative Examples 1, 4, 5, 6 were cut into rectangular specimens (4 cm×10 mm×1 mm) and subjected to fracture energy tests at room temperature.

[0090] The fracture energy is obtained by cutting a 2 mm wide notch in a 10 mm wide hydrogel, and then calculating the critical strain (εc) for rapid crack extension from the maximum stress on the stress-strain curve of the notched specimen. Then, for the stress-strain curve of the unnotched specimen, the integral area of ​​the notched specimen from the initial loading strain to the critical strain (εc) is multiplied by the initial distance (H) between the two fixtures to obtain the fracture energy value (Γ) of the specimen. The calculation formula is:

[0091]

[0092] Where σ and εc are the stress and critical strain of the hydrogel, respectively.

[0093] The results are shown in Table 1 and Figures 4-5 shown.

[0094] Table 1 Performance of hydrogels obtained in Example 1 and Comparative Examples 1 to 10

[0095]

[0096]

[0097] It can be seen from the data in Table 1 that the tensile strength and toughness of the hydrogel prepared in Example 1 are the largest, reaching 2.33137 MPa and 14.9359 MJ / m 3 It can be seen from the data changes of Comparative Examples 1 to 6 that the addition of heat-treated carbonized dopamine and sodium carboxymethyl cellulose to the hydrogel can improve the mechanical properties of the obtained hydrogel to a certain extent, but the improvement is small.

[0098] Figure 1 The stress-strain curves and partial magnifications of the hydrogels prepared in Example 1 and Comparative Examples 1 to 6 are shown in FIG. Figure 1 As can be seen from Table 1, the mechanical properties of the hydrogels prepared based on dopamine carbon dots and sodium carboxymethyl cellulose carbon dots heat-treated at 160°C increased from 0.17610MPa and 0.07024MPa to 0.26079MPa and 0.36971MPa, and the deformation also increased. This is because the carbon dots after heat treatment have optimized surface properties and graphitization, which makes them more firmly bonded to the hydrogel, thereby improving the mechanical properties. However, the improved strength is still far from satisfactory and cannot reach the ideal level. In contrast, the submicron carbon clusters prepared by heat treatment of dopamine and sodium carboxymethyl cellulose are used in hydrogels, which significantly improves the fracture strength and toughness of the hydrogels. This is because the submicron carbon clusters have a three-dimensional structure, which is interwoven with the long polymer chains, thereby greatly improving the mechanical properties of the hydrogels.

[0099] Figure 2The stress-strain curves of the hydrogels prepared in Example 1 and Comparative Examples 7 to 8 are shown in FIG. Figure 2 As can be seen from Table 1, the tensile strength and toughness of the hydrogel prepared by heat-treating the submicron carbon clusters when the mass ratio of sodium carboxymethyl cellulose to dopamine was 2:1, 1:1 and 1:2 were 0.83859 MPa, 2.33137 MPa, 0.51651 MPa and 5.22174 MJ / m 3 、14.9359MJ / m 3 2.70279MJ / m 3 This is because in the submicron carbon clusters, the long chain of sodium carboxymethyl cellulose (CMC) plays a leading role, similar to the trunk of a tree, which belongs to the supporting structure, while dopamine (DA) is similar to the branches of a tree, which belongs to the side branches. When there is too much dopamine (DA), the side branch structure (branches) is too lush, resulting in the trunk of the submicron carbon cluster being unable to withstand excessive stress and unable to effectively alleviate the expansion of cracks. On the contrary, when there is too much sodium carboxymethyl cellulose (CMC), the role of dopamine (DA) is ignored, and there are fewer side branch structures, which still cannot effectively slow down the expansion of cracks.

[0100] Figure 3 The stress-strain curves of the hydrogels prepared in Examples 1 to 3 are shown in Table 1, where 1% is Example 1, 0.75% is Example 2, and 1.25% is Example 3. Figure 3 As can be seen from Table 1, the tensile strength and toughness of the hydrogels prepared based on the mass concentration of submicron carbon clusters of 0.75%, 1% and 1.25% are 0.72117MPa, 2.33137MPa, 0.94364MPa and 5.63144MJ / m 3 、14.9359MJ / m 3 、6.15552MJ / m 3 It can be seen that when the mass concentration of submicron carbon clusters is 1%, the mechanical properties and toughness of the prepared hydrogel are the highest. This is due to the nano-interface effect brought by the nano-size of submicron carbon clusters (CCs) and the pinning effect of submicron carbon clusters on hydrogels during stretching, which greatly improves the fracture stress and elongation of the hydrogel, thereby significantly improving the toughness of the hydrogel. However, when the mass concentration of submicron carbon clusters (CCs) is further increased, the fracture stress and elongation of the hydrogel decrease instead. This is because excessive submicron carbon clusters (CCs) will cause the interface compatibility between them and the hydrogel precursor to deteriorate, making the hydrogel brittle and reducing its toughness.

[0101] Figure 4 The stress-strain curves of the hydrogels with gaps prepared in Examples 1, 2, 3 and Comparative Examples 1, 4, 5, 6; Figure 5is the fracture energy of the hydrogels prepared in Examples 1, 2, 3 and Comparative Examples 1, 4, 5, 6. Figure 4 , Figure 5 As can be seen from Table 1, the fracture energy of submicron carbon clusters with a mass concentration of 1% is the highest, reaching 126.42617 kJ / m 2 This is because the submicron carbon clusters can adapt to larger deformation and fracture, effectively dissipating energy; and they are insensitive to crack extension and can still reach a deformation of 1108%. This is because the entanglement between the submicron carbon clusters and the hydrogel precursor chains, and the effective energy dissipation of the submicron carbon clusters to the crack tip stress, making its fracture energy reach 126.42617 kJ / m 2 In addition, even for low concentrations of submicron carbon clusters, the fracture energy can reach 40.46864 kJ / m 2 This is all due to the submicron carbon clusters effectively slowing down crack propagation.

[0102] In summary, the present invention designs a new type of nanocluster as a nanofiller, and uses the pinning effect of submicron carbon clusters on cracks to prepare high-performance crystalline hydrogels. Submicron carbon clusters can effectively slow down crack propagation, relieve stress concentration at the crack tip, and eliminate notch sensitivity during the stretching process, thereby significantly improving the mechanical strength of the hydrogel. In addition, submicron carbon clusters are easy to prepare and have SP 2 The crystal nuclei endow the material with excellent conductivity and interfacial interactions (such as π-π stacking, CH-π, etc.), thereby improving the compatibility of nanoparticles (submicron carbon clusters) with the hydrogel precursor solution, promoting the uniform distribution of nanoparticles, and effectively enhancing the performance of the hydrogel.

[0103] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0104] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a super-strong and super-tough conductive hydrogel with submicron carbon clusters to slow down crack propagation, characterized in that: The steps include: Sodium carboxymethyl cellulose, dopamine and a solvent are mixed and then heat-treated to obtain a submicron carbon cluster solution; The submicron carbon cluster solution, acrylamide monomer and initiator are mixed and then subjected to polymerization reaction to obtain the super-strong and super-tough conductive hydrogel.

2. The preparation method according to claim 1, characterized in that: The solvent includes water.

3. The preparation method according to claim 1, characterized in that: The dosage ratio of the sodium carboxymethyl cellulose, dopamine and solvent is 0.5g:0.5g:100mL.

4. The preparation method according to claim 1, characterized in that: The heat treatment temperature is 160° C., and the heat treatment time is 1 hour.

5. The preparation method according to claim 1, characterized in that: The acrylamide monomers include acrylamide and N,N-methylenebisacrylamide, and the mass ratio of acrylamide to N,N-methylenebisacrylamide is 2.5:0.

004.

6. The preparation method according to claim 1, characterized in that: The initiator includes 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the submicron carbon cluster solution, acrylamide monomer and initiator is 5.625-9.375:2.5:0.

05.

8. The preparation method according to claim 1, characterized in that: The polymerization reaction conditions: UV light conditions, light intensity of 70mw / m 3 , temperature is 25±5℃, time is 2min.

9. The super strong and super tough conductive hydrogel prepared by the preparation method according to any one of claims 1 to 8.

10. Application of the super-strong and super-tough conductive hydrogel according to claim 9 in the fields of human-machine interaction interface, flexible electronics and soft robots.

Citation Information

Patent Citations

  • Preparation method of injectable directional conductive hydrogel

    CN111423600A

  • Self-adhesion anti-freezing moisturizing multifunctional conductive hydrogel as well as preparation method and application thereof

    CN117229530A

  • Flexible hydrogel based on MXene, preparation method and application of flexible hydrogel in pressure sensor

    CN118725201A

  • Carboxymethyl cellulose-based flexible wearable hydrogel material as well as preparation method and application thereof

    CN118772324A

  • Preparation method and application of ultrahigh-tensile conductive hydrogel material

    CN119119368A